EFFECTIVE PREVENTION OF DIARRHEA FOR CHILDREN IN INDONESIA: LITERATURE REVIEW - Wulandari, Yossy (ProNers, 2023)
Background: Diarrhea remains one of causes for children mortality in Indonesia. Every year it is estimated that 500,000 deaths occur in children in the world, and 10,000 deaths occur in children in Indonesia. There are several ways that have been known to prevent diarrhea, but deaths in children from diarrheal diseases are still happening. Why diarrhea still causes death in children, how to effectively prevent diarrhea in children, especially to be applied in Indonesia. Methods: Literature Review research with data analysis techniques using content analysis, articles obtained from the Google Scholar database, PubMED, proQuest.com using keywords: diarrhea in children, diarrhea, children, diarrhea prevention. Results: The results of the literature review found nine articles that matched the criteria. The analysis shows that prevention of diarrhea can be done by washing hands with soap, consuming clean food, improving water and sanitation, breastfeeding, management of feces disposal and baby diapers, measles immunization, and giving rotavirus vaccine. Conclusion: Effective prevention of diarrhea in infancy can be done by the mother's behavior in washing hands, management of excreta disposal and baby diapers, exclusive breastfeeding, and measles and rotavirus immunization. Prevention in toddlers and school-age children can be done by improving sanitation, consuming clean food, and washing hands with soap. It is estimated that the number of deaths from diarrhea decreased by 50%.